Clinical and Pulmonary CT Characteristics of Patients Infected With the SARS-CoV-2 Omicron Variant Compared With Those of Patients Infected With the Alpha Viral Strain - Yang, Naibin; Wang, Chuwen; Huang, Jiajia; Dong, Jing; Ye, Jihui; Fu, Yuan; Huang, Jingfeng; Xu, Daojie; Cao, Gang; Qian, Guoqing (Frontiers in Public Health, 2022)
Background: Omicron has become the dominant variant of SARS-CoV-2 globally. We aim to compare the clinical and chest computed tomography (CT) characteristics between patients infected with SARS-CoV-2 Omicron and the ancestral strain. Methods: Clinical profiles and chest CT images of 420 patients diagnosed as coronavirus disease 2019(COVID-19) in Ningbo first hospital between January 2020 and April 2022 were collected. Demographic characteristics, symptoms, and imaging manifestation were compared between patients infected with SARS-CoV-2 Omicron variant and ancestral strain. Results: 38 patients were identified with SARS-CoV-2 ancestral strain infection, while 382 patients were considered with Omicron variant. Compared with ancestral strain, patients infected with Omicron were younger and with higher proportion of men (P<0.001). 93(24.3%) were asymptomatic in patients infected with Omicron, while only 2(5.3%) were in those with ancestral strain. Fever(65.8%), cough(63.2%), shortness of breath(21.1%), and diarrhea(21.1%) were more common in patients infected with SARS-CoV-2 ancestral strain, while the Omicron variant were characterized with running nose (24.1%), sore throat (31.9%), body pain (13.6%), and headache(12.3%). Compared with 33(86.84%) out of 38 patients infected with ancestral strain presented with viral pneumonia in chest CT images, only 5(1.3%) among 382 patients of Omicron variant had slight focus. Moreover, the distribution of opacities in the five patients was unilateral and centrilobular, while bilateral involvement and multiple lesions located in peripheral zones of the lungs were found in most patients infected with ancestral strain. Conclusion: The SARS-COV-2 ancestral strain mainly affects the lungs, while Omicron is confined to the upper respiratory tract in COVID-19 patients.